Pressure ulcer incidence and Braden subscales: retrospective cohort analysis in general wards of a Portuguese hospital - Sardo, Pedro Miguel Garcez (2018)
Aim: To study the influence of Braden subscales scores (at the first pressure ulcer risk assessment) on pressure ulcer incidence using a univariate and a multivariate time to event analysis. Materials and methods: Retrospective cohort analysis of electronic health record database from adult patients admitted without pressure ulcer(s) to medical and surgical wards of a Portuguese hospital during 2012. The hazard ratio of developing a pressure ulcer during the length of inpatient stay was calculated by univariate Cox regression for each variable of interest and by multivariate Cox regression for the Braden subscales that were statistically significant. Results: This study included a sample of 6552 participants. During the length of stay, 153 participants developed (at least) one pressure ulcer, giving a pressure ulcer incidence of 2.3%. The univariate time to event analysis showed that all Braden subscales, except “nutrition”, were associated with the develop- ment of pressure ulcer. By multivariate analysis the scores for “mobility” and “activity” were indepen- dently predictive of the development of pressure ulcer(s) for all participants. Conclusion: (Im)“mobility” (the lack of ability to change and control body position) and (in)“activity” (the limited degree of physical activity) were the major risk factors assessed by Braden Scale for pressure ulcer development during the length of inpatient stay. Thus, the greatest efforts in managing pressure ulcer risk should be on “mobility” and “activity”, independently of the total Braden Scale score.